ANALISIS PRODUKSI DAN PENDAPATAN PADI SAWAH (ORYZA SATIVA) VARIETAS UNGGUL DI DISTRIK ORANSBARI KABUPATEN MANOKWARI SELATAN - Tito Irjaman; Kunto Wibowo; Ardha Puspita Sari (Sosio Agri Papua, 2025)
This research aims to analyze the level of production and income from upland rice farming using superior varieties, as well as to identify the main constraints faced by farmers in Oransbari District, South Manokwari Regency. Rice remains one of the most strategic staple crops in ensuring national food security. Increasing rice production largely depends on the use of high-yielding varieties and the adoption of proper cultivation technologies. This study assesses the extent to which superior rice varieties contribute to production levels and farmers’ incomes in the local context. The research employed a survey method using a census approach involving 40 farmer respondents from Oransbari. Data were collected through structured interviews using questionnaires and supported by secondary data from relevant institutions. The data were analyzed quantitatively using descriptive statistics, focusing on the average production per hectare and net farm income. The results show that the average rice production using superior varieties reached 4.38 tons/ha in Sidomulyo and 4.42 tons/ha in Oransbari. The average net income per hectare was IDR 9,155,554 in Sidomulyo and IDR 9,305,364 in Oransbari. These findings indicate that farming superior rice varieties is relatively profitable and contributes significantly to the farmers’ livelihoods in the region. Nonetheless, several challenges were identified during the cultivation process, including limited access to fertilizers, pest and disease infestations, and the lack of agricultural machinery. In conclusion, rice farming using superior varieties holds promising prospects for enhancing both production and income for farmers in Oransbari District. However, for long-term sustainability and productivity improvement, local government support is crucial. This includes ensuring the availability of agricultural inputs, expanding agricultural extension services, and implementing integrated pest and disease management programs.